2009
DOI: 10.2460/ajvr.70.3.383
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential on-farm sources of Listeria monocytogenes in herds of dairy cattle

Abstract: L monocytogenes was more prevalent in samples obtained from dairy cattle and their environment than in milk samples. Strategies to control the pathogen in dairy operations should focus on cow hygiene and sanitary milk harvesting on the farm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 42 publications
6
28
1
Order By: Relevance
“…The results have highlighted that bales may be contaminated by pathogenic and nonpathogenic Listeria species, with a predominance of L. innocua over L. monocytogenes, as also previously reported (Fenlon et al, 1989;Husu et al, 2000;Mohammed et al, 2009). This could be considered positive, even if the World Health Organization (1988) indicated that the presence of nonpathogenic species indicates that environmental conditions are favorable for the survival and growth of the pathogenic species as well.…”
Section: Discussionsupporting
confidence: 84%
“…The results have highlighted that bales may be contaminated by pathogenic and nonpathogenic Listeria species, with a predominance of L. innocua over L. monocytogenes, as also previously reported (Fenlon et al, 1989;Husu et al, 2000;Mohammed et al, 2009). This could be considered positive, even if the World Health Organization (1988) indicated that the presence of nonpathogenic species indicates that environmental conditions are favorable for the survival and growth of the pathogenic species as well.…”
Section: Discussionsupporting
confidence: 84%
“…The inter- and intra-farm movement of animals and/or farmers is an important contribution in the listeria dispersion throughout the farm [33]. In addition to the feces, [40, 42, 43], animal drinking water [42, 44, 45], feeds or feed components [40, 45], sawdust bedding, farmyard manure, soil in which fodder plants were grown, cattle feed such as silage hay cubes, beet pulp and wheat lees [46], pest and wildlife could disseminate L. monocytogenes in their feces [33, 47, 48] are possible sources and routes of L. monocytogenes infection for the animals. The success in the control of the previous sources of animal, farm or/and environmental contamination with L. monocytogenes would thereby be in the welfare of the farm animals and farm environment.…”
Section: Discussionmentioning
confidence: 99%
“…The investigation of an epidemiological link between silage feeding and listeriosis in ruminants, however, gave inconsistent results. Whilst some studies could isolate matching LM strains in brains of affected animals and silage samples, others yielded unrelated strains [92, 94, 95, 98, 101, 108, 109]. A recent study detected a higher prevalence of the bacterium in samples collected from the immediate cattle environment (feed bunks, water through and beddings) and in cattle feces than in silage challenging the view that silage is the only source of LM infection [92].…”
Section: Listeriosis In Ruminantsmentioning
confidence: 99%
“…Whilst some studies could isolate matching LM strains in brains of affected animals and silage samples, others yielded unrelated strains [92, 94, 95, 98, 101, 108, 109]. A recent study detected a higher prevalence of the bacterium in samples collected from the immediate cattle environment (feed bunks, water through and beddings) and in cattle feces than in silage challenging the view that silage is the only source of LM infection [92]. This finding is in line with reports and our own observations of outbreaks unrelated to silage feeding [110–113].…”
Section: Listeriosis In Ruminantsmentioning
confidence: 99%